Political Dynamics of the Mughal Empire: An Integrated Historical Analysis - Retisfa Khairanis; Ahmad Kholil; Wildana Wargadinata (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The purpose of this research is to holistically analyze the elements that shaped the journey of the Mughal Empire, from its heyday to its decline, in the hope of providing new insights into the pattern of dynastic rule in South Asian history. This research uses a qualitative historical method with a document analysis and literature study approach. Data were obtained from primary and secondary sources, including historical records, archives, and modern literature on Mughal politics. The results show that the rise and glory of the Mughal Empire was driven by factors such as visionary leadership (for example, Akbar who introduced a policy of religious tolerance), innovations in administration and taxation systems, and economic support through international trade. On the other hand, internal conflicts such as power struggles among heirs to the throne, mounting financial burdens due to prolonged wars, as well as resistance from other regional and religious groups were the main causes of its downfall. The implication of this research is the importance of maintaining internal stability and policy innovation in sustaining the dynasty. The contribution of this research lies in enriching the literature on the history of Islamic dynasties in South Asia, which is relevant to understanding power dynamics in multicultural and multireligious contexts.